Perceptions of barriers and facilitators in physical activity participation among women in Thiruvananthapuram City, India. (December 2016) - Mathews, Elezebeth; Lakshmi, J. K.; Ravindran, T. K. Sundari; Pratt, Michael; Thankappan, K. R.
Background: Despite the known benefits of physical activity, very few people, especially women, are found to engage in regular physical activity. This study explored the perceptions, barriers and facilitators related to physical activity among women in Thiruvananthapuram City, India. Methods: Four focus group discussions were conducted among individuals between 25 and 60 years of age, in a few areas of Thiruvananthapuram City Corporation limits in Kerala, preparatory to the design of a physical activity intervention trial. An open-ended approach was used and emergent findings were analyzed and interpreted. Results: Women associated physical activity mostly with household activities. The majority of the women considered their activity level adequate, although they engaged in what the researchers concluded were quite low levels of activity. Commonly reported barriers were lack of time, motivation, and interest; stray dogs; narrow roads; and not being used to the culture of walking. Facilitators of activity were seeing others walking, walking in pairs, and pleasant walking routes. Walking was reported as the most feasible physical activity by women. Conclusion: Physical activity promotion strategies among women should address the prevailing cultural norms in the community, and involve social norming and overcoming cultural barriers. They should also target the modifiable determinants of physical activity, such as improving self-efficacy, improving knowledge on the adequacy of physical activity and its recommendations, facilitating goal-setting, and enhancing social support through peer support and group-based activities.